2006
DOI: 10.1111/j.1365-2133.1985.tb15259.x
|View full text |Cite
|
Sign up to set email alerts
|

The sequence of events in psoriatic plaque formation after tape-stripping

Abstract: The sequence of events leading to the formation of a psoriatic plaque induced by tape-stripping was studied using light and electron microscopy. Among the earliest changes noted were increased mobility of the epidermal Langerhans cells across the basement membrane, evidence of Langerhans cell-lymphocyte interaction, and increased Langerhans cell 'activity' or 'cytotoxicity'. These changes were seen as early as 2 min after stripping and remained until the development of clinical psoriasis. Collections of epider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Tape stripping of symptomless skin has revealed that such superficial trauma initiates numerous cellular and molecular events. The sequence of events includes rapid (within 2 days) infiltration of the skin by T cells, macrophages, and DCs (Heng et al, 1985). Interestingly, the presence of CD8 þ T cells and CD11c þ mononuclear cells on day 7 correlated with the appearance of psoriatic lesions following tape stripping (Paukkonen et al, 1992).…”
Section: Parallels Between Wound Healing and Psoriatic Plaque Formationmentioning
confidence: 99%
“…Tape stripping of symptomless skin has revealed that such superficial trauma initiates numerous cellular and molecular events. The sequence of events includes rapid (within 2 days) infiltration of the skin by T cells, macrophages, and DCs (Heng et al, 1985). Interestingly, the presence of CD8 þ T cells and CD11c þ mononuclear cells on day 7 correlated with the appearance of psoriatic lesions following tape stripping (Paukkonen et al, 1992).…”
Section: Parallels Between Wound Healing and Psoriatic Plaque Formationmentioning
confidence: 99%
“…Therefore, the early therapy for psoriasis is crude coal tar or a combination of coal tar and ultraviolet irradiation, both of which aim to inhibit keratinocyte proliferation and then restore normal epidermopoiesis. 1,2 Few years later, retinoids were also found to efficiently inhibit the proliferation of keratinocytes and then used to treat psoriasis. 3 Therefore, keratinocytes were originally consider as a main driver of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…The histology of lesional skin from patients with psoriasis demonstrates that epidermal keratinocytes in lesional skin are hyperproliferative, and excessive immune cells infiltrate into the dermis and epidermis. Therefore, the early therapy for psoriasis is crude coal tar or a combination of coal tar and ultraviolet irradiation, both of which aim to inhibit keratinocyte proliferation and then restore normal epidermopoiesis 1,2 . Few years later, retinoids were also found to efficiently inhibit the proliferation of keratinocytes and then used to treat psoriasis 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In 1985, Heng et al [3] attempted to describe the microscopic sequence of events associated with psoriasis by studying the different stages of psoriatic plaques induced by tape-stripping. At the time, the research concluded that the proliferation of the epidermis was maintained and clearly identified.…”
Section: Introductionmentioning
confidence: 99%